2022
DOI: 10.1101/2022.05.22.492937
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Targeting acetyl-CoA metabolism attenuates the formation of fear memories through reduced activity-dependent histone acetylation

Abstract: Histone acetylation is a key component in the consolidation of long-term fear memories. Epigenetic enzymes involved in histone acetylation, including histone acetyltransferases and deacetylases, have been put forward as potential pharmacological targets in the treatment of pathological fear memories, such as those that underlie post-traumatic stress disorder (PTSD). However, these enzymes typically play a ubiquitous role in gene regulation, which precludes the clinical use of systemic manipulations. Recently, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 77 publications
1
1
0
Order By: Relevance
“…1B). In accordance with the established role of ACSS2 to promote histone acetylation (16)(17)(18), we observed increased levels of transcription-linked H3K9ac and H3K27ac in neurons transduced with AAV.ACSS2 compared to vector control (Fig. 1, C to F).…”
Section: Acss2 Upregulation Maintains Histone Acetylation and Synapti...supporting
confidence: 87%
See 1 more Smart Citation
“…1B). In accordance with the established role of ACSS2 to promote histone acetylation (16)(17)(18), we observed increased levels of transcription-linked H3K9ac and H3K27ac in neurons transduced with AAV.ACSS2 compared to vector control (Fig. 1, C to F).…”
Section: Acss2 Upregulation Maintains Histone Acetylation and Synapti...supporting
confidence: 87%
“…In neurons, histone acetylation can be heavily dependent on the activity of ACSS2 (16). We have shown that ACSS2 resides on chromatin generating acetyl-CoA to supply key histone acetyltransferases (HATs) (16,17), allowing rapid upregulation of critical neuronal genes central to learning and memory (16,18). ACSS2 knockout leads to animals defective in memory; upregulation of ACSS2 has effects to boost some synaptic genes in an amyloid-beta expressing mouse (19).…”
Section: Introductionmentioning
confidence: 99%